Current treatment options for autonomic, cognitive and emotional disorders in patients with asthenic syndrome treated with recognan (citicoline) - Nemkova, S A; Semenov, D V; Petrova, E A; Savchenko, D V; Zavadenko, N N; Vozvyshaeva, M Yu (Zhurnal nevrologii i psikhiatrii imeni S.S. Korsakova, 2019)
To study the efficacy of recognan (citicoline) in the treatment of cognitive, emotional, autonomic, asthenic disorders in patients with asthenic syndrome. Thirty-eight subjects (17 men and 41 women), mean age 27.75±12.05 years, with asthenic syndrome (ICD-10 F48.0 - Neurasthenia) were studied. The sample was randomized into 2 subgroups: the main group (n=20) received oral therapy with recognan (100 mg in 1 ml) for 30 days, while the daily dosage was 500 mg (5 ml). In the control group (n=18), no drug therapy was performed. Patient's state was assessed with a large battery of psychological tests and psychometric scales. The follow-up period was 30 days. All participants were examined three times (initially, in the middle of the study (day 15), in the end of the study (day 30)). Asthenic syndrome was detected in 100% of the patients (total asthenia was noted in 70%, decreased activity in 70%, decreased motivation in 40%, physical asthenia in 45%, mental asthenia in 50%). Recognan (citicoline), used for 2 weeks or one month, has a positive effect on the compensation of autonomic, asthenic cognitive and emotional disorders and increases stress resilience of the patients.